THU0583 Pain interference associated factors in a cohort of finnish young adults with juvenile idiopathic arthritis. (12th June 2018) - Rebane, K.; Orenius, T.; Ristolainen, L.; Relas, H.; Kautiainen, H.; Luosujärvi, R.; Säilä, H.; Aalto, K.
Abstract : Background: Pain is one of the most distressing and persisting features of JIA and frequently interferes with everyday life. Objectives: This study was conducted to find out the factors associated with pain interference in young adults (aged 18 to 30 years) with JIA. Methods: 195 adult patients with JIA were eligible for the study. Associations between patients reported outcome data and pain interference were examined. Sociodemographic and clinical data were analysed. Pain interference was measured by a single item from the RAND 36 questionnaire. Five response categories were coded into different groups: patients reporting "extremely" and "quite a bit" or "moderate" were classified having significant pain interference; "a little bit" as having minor pain interference; and "not at all" as having no pain interference. Functional disability was measured by HAQ, depressive symptoms were measured by Beck Depression Inventory-II, self-esteem was assessed by Rosenberg Self-Esteem Scale, and anxiety was assessed by PASS-20. Leisure time physical activity (LTPA) metabolic equivalent (MET) score was calculated. Results: Pain intensity scores were higher in patients expressing significant pain interference (mean 5.3, SD 2.1) and minor pain interference (mean 2.8, SD 2.09); p for linearity <0.001, thus the mean pain intensity for the whole study group was quite low (mean 2.3, SD 2.3). Of the 195 patients 98 (50.3%) reported no pain interference, 59 (30.3%) reported minor pain interference, and 39 (20%) reported significant pain interference. We found that pain interference was associated with older age (p=0.029), female gender (p=0.028) and receiving antirheumatic treatment (p=0.032), analgesics (p<0.001), antidepressants (p=0.008), and opioids (p<0.001). Also cohabiting (p=0.003), LTPA MET (p=0.032), smoking (0.006), being more disabled (p<0.001), having fewer leisure time activities (p<0.001) or having co-morbidities (p=0.006), and headache (p<0.001) were associated with having pain interference. Higher anxiety scores were associated with more pain interference (p<0.001). When controlling for gender, age, depression, LTPA MET, disability, life situation, disease remission, analgesics, antidepressants, and pain intensity, all subscales in PASS-20 were significantly associated with higher pain interference levels: cognitive anxiety (p=0.004), escape/avoidance (p<0.001), fear (p=0.001), psychological anxiety (p=0.016). Conclusions: Half of the JIA patients reported pain interference, and they also expressed higher pain scores. Age, gender, using antirheumathic drugs, antidepressants, analgesics or opioids, cohabiting, lower LTPA MET score, disability, smoking, co-morbidities, lack of activities, and suffering anxiety were most significantly related to pain interference. Our study highlights the need to develop better strategies for pain-relieving interventions and for supporting patients' health-behaviour in order to achieve better pain outcome in young adults with JIA. Disclosure of Interest: None declared